Therapeutic Adherence of Patients with Type 2 Diabetes Mellitus in Four Health Areas of the Country - Addys María Díaz Piñera; Armando Rodríguez Salvá; Fernando Jesús Achiong Estupiñán; Dania Lidia Cardona Garbey; Geominia Maldonado Cantillo; Esteban Augusto Londoño Agudelo; Patrick Van der Stuyft (Revista Finlay)
Foundation: non-compliance with treatment by diabetic people not only worsens the prognosis, but also their quality of life. Objective: to characterize therapeutic adherence in type 2 diabetic patients belonging to four health areas, from two municipalities in Cuba. Methods: a descriptive and cross-sectional study was carried out in two health areas of the municipalities of Cárdenas and Santiago de Cuba, in the period January - August 2019. The universe was represented by 1091 diabetic people who recovered from a previous study carried out between 2015 and 2016 in the same health areas. They underwent anthropometric measurements, blood pressure, glycated hemoglobin and a questionnaire was applied. Variables were studied: sociodemographic (age, sex, skin color, occupation, level of education, cohabitation), risk factors and comorbidities, pharmacological and non-pharmacological treatment and their relationship with adherence. Categorical variables were presented as frequencies and percentages. Results: adherence was 70.7 %, statistically related to white skin color, high level of education, control of glycated hemoglobin according to age and value less than 7 %, as well as not suffering from comorbidities such as cardiovascular diseases, chronic respiratory diseases, dyslipidemia, no consumption of alcoholic or sugary beverages. Conclusions: the non-availability of medications in the pharmacy, forgetting to take them and at the established times were the main barriers reported by patients, this must be taken into account to have a favorable impact on the control of diabetes mellitus.